Описание и классификация форм сохранности окаменелостей из коллекций Музея пермской системы Пермского государственного национального исследовательского университета (ПГНИУ) - Bashurova I. A., Старцева А. А., Азанова П. Д., Ozhgibesov V. P. (Scientific studies: theory, methodology and practice, 2018)
Summary: on material of educational collections, and also paleontological collections from an exposition of the museums of Department of the Regional and Oil and Gas Geology of the Perm State University forms of safety of fossils was described. Two systems of the description of forms of safety are compared: domestic and foreign, based on English-speaking terminology.
Keywords: музей; museum; палеонтология; paleontology; minerals; коллекции; collections; ископаемые; формы сохранности; палеонтологическое описание; окаменелости; фоссилии; forms of safety; fossils; paleontological description